Fostering School-Age Teenagers: An Effort to Repress Child Marriage in The Perspective of Talcott Parsons - Yolanda, Yuke; Hasanudin, Fuat (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
This research has examined the influence of Fostering School-Age Teenagers Program (BRUS) in repressing child marriage rates in Sleman Yogyakarta, which is analyzed based on Talcott Parsons' functional structural theory through four stages, namely AGIL (Adaptation, Goal attainment, Integration, and Latency) against the BRUS program implementation guidelines contained in the Decree of the Director General of Islamic Public Guidance Number 1012 of 2022. The method used by the author in this research is a quantitative method, with a sociological approach, using the Respondent Achievement Level (RAL) formula with the help of the SPSS version 29 program and Microsoft Excel which is adjusted to the efforts aligned with the 4 stages in the AGIL concept. Respondents in this study were students who had participated in Fostering School-Age Teenagers Program in several Senior High Schools / Equivalents in Sleman Regency with a sample size of 487 students who had an age range of 15-19 years. The results of this study found that in general, the Adaptation, Goal attainment, and Integration stages were only realized in 11.9% of high schools in Sleman. In addition, only 4% of high schools have reached the Latency stage. Then the effect of this Fostering School-Age Teenage Program in repressing the desire for child marriage in teenagers is on average 77.58% with a good enough category for 16 SMA / equivalent in Sleman. However, in the aspect of decision-making in teenagers such as decisions in lectures, marriage, and careers is still as evidenced by 40% of teenagers who have participated in BRUS still have difficulty making decisions. BRUS still experience difficulties in making decisions.